Euthanasia in Human Rights Perspective: The Dialectic Between the Right to Live and the Right to Die - Adawiyah, Robi'atul; Amanda Putri, Kharisma (Media Hukum Indonesia (MHI), 2025)
The discourses and dialectics regarding euthanasia have yet to find an end. Because there are 2 human rights values that face each other: the right to life and the right to die. This article seeks to photograph euthanasia in a human rights perspective by stressing on the dialectic between the right to life as an absolute right and the right to self-determination as an embodiment of respect for human autonomy and dignity. This study belongs as a normative juridical research with a legislative and conceptual regulation approach in which legal materials are obtained through library study and internet searches which are then analyzed and interpreted deductively. Study results show that the right to life is a fundamental right that has been recognized in international human rights documents and national legislative regulations. In the perspective of the right to life, the act of euthanasia cannot be justified because every act either directly or indirectly that ends a person’s life is contrary to the principle of protection of the right to life. In the perspective of the right to die, the act of euthanasia derives its legitimacy based on the school of utilitarianism and the prolonged suffering experienced by the human individual actually clashes with the concept of the right to life itself. The prospect of regulating euthanasia in the ius constituendum is to constitute a more humanistic, ethical, and rational regulation of legislation focused on the protection of patients’ rights to choose or refuse medical treatment, the strengthening of medical codes of ethics, and the affirmation of the boundaries between medical actions that are considered reasonable.